PENGARUH POHON INDUK DAN BAHAN STEK TERHADAP PERTUMBUHAN STEK CABANG TIMOHO (Kleinhovia hospita L) - Lukman Hakim; Yuliah Yuliah; Hamdan Adma Adinugraha (Jurnal Pemuliaan Tanaman Hutan, 2019)
Timoho (Kleinhovia hospita L) is a rare plant that has high economic and cultural value for the Javanese people, especially in Yogyakarta. Timoho wood has a beautiful pattern called pelet and is used as a raw material for keris sheath. In Javanese culture, the keris is a masterpiece culture that is used as a weapon, spiritual object and complementary traditional events such as marriage. In Yogyakarta, Timoho trees are difficult to find, currently, so that plant propagation in a generative way also has difficulty due to scarcity of seeds. Therefore, it is necessary to conduct Timoho propagation research through vegetative methods. The purpose of this study was to determine the relationship between the origin of stem cuttings from three Timoho mother trees and the stem section (base, middle, and end) to the success of Timoho stem cuttings. Stem cuttings come from three Timoho trees in the Arboretum of the Center for Forest Research and Development of Forest Biotechnology and Tree Improvement Yogyakarta. The research method used a nested experimental design using 3 mother trees and 3 stem parts (base, middle and end) which were nested in the mother tree. The characters observed were percentage of shoots, number of shoots, length of shoots, and number of leaves. The results showed the percentage of live cuttings varied from 10.9-60.0%, number of shoots 1-7 pieces, number of leaves 3-26 strands and length of shoots 2.00-17.7 cm. The mother tree treatment has a significant effect on the percentage of sprouts and shoot length, while the cuttings material has a significant effect on the length of shoots at the cuttings measurements of the age of 2 months since planted in polybags.